2018
DOI: 10.34190/ejel.16.1.2367
|View full text |Cite
|
Sign up to set email alerts
|

Students’ and Instructor’s Perspective on the use of Blackboard Platform for Delivering an Engineering Course

Abstract: The use of Information Technology (IT) has been growing over the years in various human endeavours. It has also been adopted in education sector for teaching and learning. Various studies have been conducted to assess the effectiveness and acceptance of e-learning strategy by students. In particular, the current research is an attempt to obtain students’ and instructor’s perspective on the use of Blackboard software. The technology is a course management system used in a blended learning mode to deliver a thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…However, some studies have revealed some issues that may interfere with the ability of students and instructors to collaborate effectively over the Blackboard platform [9,10].…”
Section: A the Use Of Lms In Educationmentioning
confidence: 99%
“…However, some studies have revealed some issues that may interfere with the ability of students and instructors to collaborate effectively over the Blackboard platform [9,10].…”
Section: A the Use Of Lms In Educationmentioning
confidence: 99%
“…BB is used worldwide by many colleges and universities with potential benefits (Beatty, 2010). It is considered a flexible and easily accessible educational platform (Uziak et al, 2018;Beatty,2010), and users can access BB at any place via the world wide web (WWW). Among the most distinctive features of BB are efficient functionality, usability, standardization, security, student-teacher interaction, and class management.…”
Section: Blackboard (Bb)mentioning
confidence: 99%
“…Collaboration and communication are regarded as the best LMS features embedded in BB (Bradford et al, 2007;Uziak et al, 2018;Chen, Dobinson & Kent, 2020). Since the teacher-student interaction during the pandemic has been of utmost importance, BB provides access for the teachers to communicate with students by asynchronous and synchronous platforms.…”
Section: Blackboard (Bb)mentioning
confidence: 99%
“…Students emphasise the roles of lecturer interaction and attitude to better deal with their emotions, thereby enhancing the learning process (Hernández-Amorós & Urrea-Solano, 2017). Lecturers have found VLE as an appropriate medium of communication with students that increase their interaction (Uziak et al, 2018). (Hernández-Amorós & Urrea-Solano, 2017) revealed that once lecturers received training on handling students' emotions, students reacted positively to the lecturers' interactions.…”
Section: Lecturer's Interactionmentioning
confidence: 99%